Residual weld stresses in stiffener-to-deck plate weld of an orthotropic steel deck. (August 2019) - Van Puymbroeck, Evy; Van Staen, Gilles; Iqbal, Nouman; De Backer, Hans
Abstract: A three-dimensional finite element welding simulation procedure is developed with the software Siemens NX and solver type SAMCEF in order to determine the residual stresses of a welded component of an orthotropic bridge deck. The welding process of a deck plate which is welded to a closed trapezoidal stiffener is simulated. A decoupled thermal-mechanical analysis is performed. During the thermal analysis, the temperatures introduced by the passage of the welding torch are calculated for different time steps. This temperature field is used during the thermal analysis to determine the residual welding stresses for the same time steps. The decoupled thermal-mechanical analysis gives the distribution of the residual stresses. For the transverse direction, there are tensile yield residual stresses on the deck plate near the weld region. In between the welded webs of the stiffener, there are compressive residual stresses. For the longitudinal stiffener, there are again tensile yield residual stresses near the weld which decrease at a greater distance and turn into compressive residual yield stresses. For the longitudinal direction, there are tensile yield stresses present near the weld and a compressive residual stress in the middle of the deck plate. The stiffener only shows a small tensile stress peak near the weld root and along the stiffener there are small tensile residual stresses. The results from the finite element analysis are validated by experimental measurements with the incremental hole-drilling method. A residual stress distribution for the top and bottom side of the deck plate and the longitudinal stiffener is determined for both the longitudinal and transverse direction.